Non-Income Inequality Among Rural Households in Nigeria (2011)
Inequality is an important factor in understanding the welfare of rural households. Most discussions on inequality have focused primarily on income to the exclusion of non-income dimensions such as skills, education, political participation, health and life expectancy. Knowledge of non-income inequality will enhance the understanding of the key welfare attributes of Rural Households (RHs). The extent of and factors affecting non-income inequality among households in rural Nigeria were investigated. The data were from 2006 Core Welfare Indicator Questionnaire Survey obtained by National Bureau of Statistics (NBS). Respondents were selected using a two-stage cluster sampling technique involving the selection of 10 Enumeration Areas (EA) from each Local Government Area followed by the selection of 10 housing units from each EA. Of the 77,400 households sampled by NBS, 59,567 were rural. Data set used included socio-economic characteristics, housing condition, assets, household educational attainment, access to health care services and political participation. Generalized Entropy, Shapley decomposition and ordered probit regression were employed in analyses (p=0.05) Mean age for respondents (RHs) was 48.7±15.3 years; Farming Households (FHs) and Non-Farming households (NFHs) were 48.7±16.2 and 48.7±14.9 years respectively. Mean household size for RHs was (4.9±2.1); FHs (4.9±3.2) and NFHs (4.8±1.9) respectively. Education, political and health inequalities among RHs were 0.409, 0.196 and 0.320 respectively. Education inequality was higher among FHs (0.413) compared with NFHs (0.407). There was higher political inequality among FHs relative to NFHs with indices of 0.200 and 0.195, respectively. Health inequality was also higher among FHs (0.327) than NFHs (0.300) respectively. North-West zone had the highest education inequality for both FHs (0.432) and NFHs (0.412). Political inequality was highest in the South-East zone for both FHs and NFHs with indices of 0.220 and 0.213 respectively. North-East zone had the highest health inequality at 0.350 and 0.319 for FHs and NFHs respectively. Between 82.7% and 95.4% of education, political and health inequalities across the zones were explained by within group disparity while the rest was by between group dynamics for all RHs. Sanitation index, asset base index, house ownership and condition index increased probability of RHs having high educational attainment by 0.004, 0.003 and 0.029 respectively. Household size and age of household head reduced educational inequality by 0.002 and 0.001. A percentage change in asset base index as well as house-ownership and condition index increased political inequality among RHs by 0.001 and 0.001 respectively. One percent increase in household size and age reduced it by 0.001 and 0.001 respectively. The probability of RHs having high access to health care increased by 0.002, 0.002 and 0.022 with 1% increase in sanitation index, asset base index, house ownership and condition. However, household size and age reduced it by 0.004 and 0.001 respectively. Educational inequality was highest across regions in the country when compared with other non-income welfare attributes. Households in the North are more politically balanced but with higher level of inequality in education and health. Furthermore, farming households are disadvantaged as they have higher inequalities in education, political participation and health care.